RELATIONS BETWEEN TURKISH STATE AND KURDISH SOCIETY IN TURKEY: پەيوەندييا دەولەتا تركيا و جڤاكىَ كوردى ل تركيا - Tahir, Hawar Khalil (Journal of Duhok University, 2018)
A state-society relation in Turkey is the aim of this research which it divided on two different periods: between 1923 until 2002 and from 2002 until 2014. During these two different periods the Turkish state has implemented two distinct policies regarding to the Kurdish rights. Throughout the first period, under the shadow of secularism, isolation process has instigated towards the Kurdish society. In the second period, under the shadow of APK, some basic cultural norms have transformed in favor of the Kurds. This research is a comparative study of the Kurdish rights in Turkey during so-called two different periods.